Logosowy charakter wiary według Josepha Ratzingera – Benedykta XVI - Krzysztof Góźdź (Polonia Sacra)
According to Ratzinger, faith is not a blind theory or an outdated concept. Neither is it an intricate philosophical system. Instead, he defines faith as “finding a way towards wisdom, rationality and factuality; [that is] a way towards perceiving reality in full.” This kind of faith becomes a gate to the communion with God, Lord of history and Lord of the universe. Thus, faith is a personal and not a material category. It belongs to the world of personal and not material relations. “Faith is a decision to be with Lord, and to live with Him.” Nevertheless, the decision cannot be a blind choice. It must rest on Logos, so that it truly is a fact-based reality. Claiming that, Ratzinger discloses his great philosophical mind. He skilfully avoids fideism, subjectivism or irrationalism in comprehending faith. He can see faith as the highest level of existence of the mind, reason, will, love and man self-fulfilment in the Holy Trinity.